Pulmonary Hypertension in Bronchopulmonary Dysplasia - Berkelhamer, Sara K. (Semin Perinatol, 2013)
Pulmonary hypertension (PH) is a common complication of neonatal respiratory diseases including bronchopulmonary dysplasia (BPD), and recent studies have increased awareness that PH worsens the clinical course, morbidity and mortality of BPD. Recent evidence indicates that up to 18% of all extremely low birth weight infants will develop some degree of PH during their hospitalization, and the incidence rises to 25–40% of infants with established BPD. Risk factors are not yet well understood, but new evidence shows that fetal growth restriction is a significant predictor of PH. Echocardiography remains the primary method for evaluation for BPD-associated PH, and the development of standardized screening timelines and techniques for identification of infants with BPD-associated PH remains an important ongoing topic of investigation. The use of pulmonary vasodilator medications such as nitric oxide, sildenafil, and others in the BPD population is steadily growing, but additional studies are needed regarding their long-term safety and efficacy.